Assessment of occupational risks from exposure to suspended ultrafine particles of industrial aerosol for workers of a metallurgical enterprise - Sharavara, L. P.; Dmytrukha, N. M.; Andrusyshyna, I. M. (Modern medical technology, 2025)
Aim. To assess occupational risks from exposure to suspended ultrafine particles of industrial aerosol for workers of a metallurgical enterprise. Materials and methods. The study of the content of suspended particles was carried out at the workplaces of metallurgical production workers using a portable scanning spectrometer Nanoscan 3910 (USA). Their chemical composition was studied by optical emission spectrometry with inductively coupled plasma (OES-ICP) on the device “Optima 2100 DV” manufactured by “PerkinElmer” (USA). Based on the results obtained, carcinogenic and non-carcinogenic risks were calculated. Results. It was established, that in the air of the working area of the open-hearth furnace steelworker, the total numerical concentration of suspended particles was 6.9 × 104 (4.0 × 104; 8.0 × 104) particles/cm3, in the air of the working area of the blast furnace – 5.1 × 104 (4.5 × 104; 7.8 × 104), in the air of the sinter plant working area – 2.4 × 104 (2.1 × 104; 5.1 × 104). All indicators exceeded the total numerical concentration of suspended particles of control workers and were statistically significantly higher (p ˂ 0.001). The composition of suspended particles included Si, Al, P, Fe, Ca, Mg, Cr and Ni, which is due to the type of technological process. Exceedances of hygienic standards was observed for P, Cr and Ni. The calculated carcinogenic risk indicators for workers from exposure to chromium and nickel were high. The hazard coefficients from exposure to suspended particles with element densities >6 kg/m3 and <6 kg/m3 for an open-hearth furnace steelworker were HQ = 3.15 and HQ = 1.57, for a blast furnace worker – HQ = 2.54 and HQ = 1.27, for a sinter plant worker – HQ = 3.15 and HQ = 1.57, respectively. The greatest non-carcinogenic risk was caused by particles up to 64 nm in size. The risk excess factor at the workplace of an open-hearth furnace steelworker, compared with workers in the control group, was 224.8 times, at the workplace of a blast furnace worker – 61.9 times, and at the workplace of a sinter plant worker – 12.9 times. Conclusions. During the production of sinter, cast iron and steel, suspended particles of combined chemical composition are formed at the workplaces of workers. The obtained carcinogenic risk values from exposure to chromium and nickel for all workers were high. The hazard coefficients from exposure to suspended particles for almost all workers exceeded unit, that can be considered unacceptable. The greatest risk, depending on the size, for all workers was posed by the smallest particles (≤64 nm).